1984
DOI: 10.1203/00006450-198407000-00001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ketone Bodies and Fatty Acid on Intestinal Glucose Metabolism during Development

Abstract: Summaryfrom glucose was markedly decreased and lactate production increased. In the present study we investigated developmeni.al Glucose oxidation by developing rat intestine changed dramat-change in glucose metabolism to C 0 2 , lactate, and pyruvate by ically during the period o f suckling and weaning. After weaning, intestine during the time of suckling and weaning, glucose oxidation to C 0 2 by intestinal slices increased over 3-fold. This was associated with an increase in lactate production from glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
1

Year Published

1986
1986
1998
1998

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
1
13
1
Order By: Relevance
“…This would suggest that glucose utilization is low in infant rats, and this is generally true. However, the data reported by Kimura et al (10) were obtained for the whole intestinal wall and not the isolated mucosa, and it is more than likely that the muscular layer of the gut metabolizes glucose differently than the mucosa. This is borne out by the absence of PEPcK in the muscular layer and the much greater contents of cyclic AMP in this layer in comparison to the mucosa (9).…”
Section: Discussioncontrasting
confidence: 48%
“…This would suggest that glucose utilization is low in infant rats, and this is generally true. However, the data reported by Kimura et al (10) were obtained for the whole intestinal wall and not the isolated mucosa, and it is more than likely that the muscular layer of the gut metabolizes glucose differently than the mucosa. This is borne out by the absence of PEPcK in the muscular layer and the much greater contents of cyclic AMP in this layer in comparison to the mucosa (9).…”
Section: Discussioncontrasting
confidence: 48%
“…In contrast, the rate of glucose completely oxidized remained constant. In intestinal slices from suckling rats, the rate of glucose oxidation to CO, represents 2 to 5% of the rate of glycolysis (23,47). However, in contrast to the pig situation, the rates of glycolysis and glucose oxidation significantly increase at weaning in rat intestinal slices.…”
Section: Darcy-vrillon Et Almentioning
confidence: 85%
“…We used a tissue slice technique rather than homogenates so that endogenous pools of substrate and metabolic controls present at the time of animal death were left intact (5,6). A number of criticisms of the tissue slice technique have been raised, including nonuniform diffusion of substrate.…”
Section: Tissue Preparations Sprague Dawley Rat Mothers With Littersmentioning
confidence: 99%
“…Less than 20% comes from fatty acids, glucose, and lactate combined, while 50-60% comes from ketone bodies. Previously, we reported that the oxidation of substrates (glucose, pyruvate, acetate, fatty acids) entering the citric acid cycle at the level of acetylCoA is suppressed during the suckling period (6). Neonatal rat pups consume a majority of their calories in the form of fatty acids while they suckle and the liver ketogenesis from fatty acid oxidation results in high serum levels of 3-hydroxybutyrate and acetoacetate.…”
mentioning
confidence: 99%
See 1 more Smart Citation